Contamination Risk in Indonesian Youtube Videos on Personal Protective Equipment for Corona Virus Disease - Laksita Barbara; Mareta Dea Rosaline; Akhiyan Hadi Susanto (Lembaga Penerbitan Universitas Esa Unggul, 2021)
AbstractThere are numbers of Indonesian Youtube Videos that show steps to wear and remove Personal Protective Equipment (PPE) for Corona Virus Disease (COVID19). However, the conformity with the current guidelines remains unknown. This paper aims to determine the validity of these videos based on the World Health Organization (WHO) guidelines. We searched on the Youtube website for videos in donning and doffing PPE for droplet precaution and selected the videos using inclusion and exclusion criteria. Included videos were then evaluated with a checklist derived from WHO course on donning and doffing PPE for COVID-19 and WHO recommendation on PPE for Covid-19. The search that was undertaken resulted in 66 videos, and 40 videos were included for evaluation. There is no significant difference in the donning and doffing score between account types (personal, organizational/institutional, news). The average number of viewers of all videos is more than 2700 viewers. The average score of donning is less than 70% of the total score, and the average doffing score is under 65%. The vast majority of the videos do not follow the WHO recommendation on the PPE type and use more equipment than recommended. There are several contamination risks shown by the videos. Indonesian Youtube videos on PPE procedures for COVID-19 must be selected carefully to be used as an instructional or educational media since most of it presents a high risk of cross-contamination.Keyword: personal protective equipment, audiovisual, cross-contamination, trainingAbstrakTerdapat video dalam Bahasa Indonesia yang terkait cara memakai dan melepaskan Alat Pelindung Diri (APD) untuk Corona Virus Disease (COVID19). Namun, kesesuaian video terhadap pedoman terkini belum diketahui. Penelitian ini bertujuan untuk menentukan validitas video berdasarkan pedoman World Health Organization. Kami menelusuri Youtube untuk memperoleh video instruksi mengenakan dan melepas APD pencegahan kontaminasi droplet dan menyeleksi video tersebut berdasarkan kriteria inklusi dan eksklusi. Video yang telah diseleksi kemudian dievaluasi menggunakan checklist yang diturunkan dari langkah-langkah yang ditunjukan dalam kursus APD COVID-19 yang disediakan oleh WHO, serta rekomendasi APD dari WHO. Penelusuran Youtube menampilkan 66 video, dan dipilih 40 video yang sesuai dengan kriteria kelayakan. Tidak terdapat perbedaan signifikan dalam skor mengenakan dan melepaskan APD antara akun personal, organisasi/institusi, dan berita. Rata-rata jumlah penonton video adalah lebih dari 2700. Skor rata-rata pemakaian APD kurang dari 70% dari skor total, dan skor pelepasan APD kurang dari 65%. Sebagian besar video tidak mengikuti rekomendasi WHO dalam pemilihan tipe PPE dan menggunakan alat yang lebih banyak dari yang direkomendasikan. Terdapat sejumlah risiko kontaminasi yang dapat diobservasi dari langkah-langkah yang ditunjukan dalam video. Video Youtube prosedur APD untuk COVID-19 perlu diseleksi dengan cermat untuk digunakan sebagai media instruksi maupun pendidikan karena sebagian besar menunjukan risiko tinggi kontaminasi silang.Kata Kunci: alat pelindung diri, audiovisual, kontaminasi silang, pelatihan